2006
DOI: 10.1093/ndt/gfl147
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis dose (Kt/V) and clearance variation sensitivity using measurement of ultraviolet-absorbance (on-line), blood urea, dialysate urea and ionic dialysance

Abstract: The UV-method gives a similar response to clearance reduction compared with the other methods when comparing dialysis dose. The high sampling rate by continuous monitoring of UV-absorbance allows evaluation of the clearance process during dialysis and gives immediate feedback to on-line adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 17 publications
4
56
0
1
Order By: Relevance
“…An innovative optical method determines the concentration of cleared waste solutes by measuring UV absorbance of the dialysate [3]. The close correlation between dialysate UV absorbance and the removal of urea allows continuous calculation of Kt/V values [4]. Several studies have validated this method, showing a close correlation of approximated Kt/V values to the laboratory-determined Kt/V value based on urea analyses in blood samples [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An innovative optical method determines the concentration of cleared waste solutes by measuring UV absorbance of the dialysate [3]. The close correlation between dialysate UV absorbance and the removal of urea allows continuous calculation of Kt/V values [4]. Several studies have validated this method, showing a close correlation of approximated Kt/V values to the laboratory-determined Kt/V value based on urea analyses in blood samples [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The close correlation between dialysate UV absorbance and the removal of urea allows continuous calculation of Kt/V values [4]. Several studies have validated this method, showing a close correlation of approximated Kt/V values to the laboratory-determined Kt/V value based on urea analyses in blood samples [4,5]. A potential advantage of the optical online system is its continuous monitoring of Kt/V, which may help to immediately address intra-dialytic variations in dialysis adequacy as caused by needle displacement, recirculation, hypotension and clotting [6].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that UV absorptions at 280, 285 and 297 nm have a close correlation with urea-based dialysis dose estimation [11,13,14]. This made it possible to develop a clinically validated online dialysis adequacy monitoring system [15].…”
Section: Introductionmentioning
confidence: 99%
“…drain tube) of the dialysis machine, as in earlier studies [15,16,17], with all spent dialysate and ultrafiltrate passing through a rectangular optical flow cuvette (JASCO) with a path length of 10 mm. To find out if it would be possible to create a specific single-wavelength model for phosphate similarly to an earlier study [17], a single wavelength of 297 nm was selected using a bandwidth of 2 nm. The sampling frequency was set to 30 samples/min (= 0.5 Hz).…”
Section: Methodsmentioning
confidence: 99%